Acute myelomonocytic leukaemia complicated by an acute aortic thrombosis. - Leong, K.W.; Bosco, J.J.; Shaik, I.B. (1995)
Acute aortic thrombosis is a rare condition, occurring mainly as a result of trauma or atherosclerosis and occasionally secondary to hypercoagulable states. We report a patient with relapsed acute myeloid leukaemia who developed an unusual complication, acute aortic thrombosis.